Self-humidified operation of a PEM fuel cell using a novel silica composite coating method. (22nd January 2022) - Angayarkanni, R.; Ganesan, Aristatil; Dhelipan, M.; Karthikeyan, S.; Mani, N.; Thiyagarajan, P.
Abstract: A proton exchange membrane fuel cell operating with no external humidification support was successfully reported using a novel silica composite layer on the anode side (Pt/C/SiO2 /Nafion). The nanosilica derived from tetramethoxy silane (TMOS) provided excellent porous morphology to retain water and hydrate protons. This layer provides a well-humidified environment for protons and easy proton transfer from the catalyst surface to the membrane electrolyte. The characteristics of the silica composite layer were investigated by various characterization methods: SEM, XRD, TEM, XPS, EIS, and TGA. A single cell fabricated with the anode containing this new silica composite layer showed a performance of 0.9 W/cm 2 which is two folds greater when tested with the commercial catalyst MEA (0.45 W/cm 2 ). MEA delivered a constant output power (at 0.6 V) under dry and humidified gas conditions which shows excellent electrochemical stability and durability. Graphical abstract: Image 1 Highlights: PEMFC operating without external humidification support. Investigations on novel Silica Composite layer Self-humidified MEA. Tested at constant power output in both dry and humidified conditions. Delivered two folds higher performances compared to commercial MEA.